2010
DOI: 10.1007/s00535-010-0235-3
|View full text |Cite
|
Sign up to set email alerts
|

CD133 expression is a potential prognostic indicator in intrahepatic cholangiocarcinoma

Abstract: CD133 expression tended to be related to higher incidences of intrahepatic metastasis and positive expression of hypoxia-inducible factor-1alpha; furthermore, it was independently related to worse prognosis. Therefore, the CD133 expression is a potential prognostic indicator in IHCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 27 publications
9
52
0
Order By: Relevance
“…However, few new markers associated with prognosis or malignant behavior of ICC has been determined (Oishi et al 2012;Shimada et al 2010). In this study we studied Nogo-B, which has recently been identified as a potential marker of hepatic fibrosis (Zhang et al 2011;Gao et al 2013;Tashiro et al 2013;Men et al 2015) and as a potential enhancer of bile duct proliferation (Zhang Each survival rate is shown as % value, based on our analytical software.…”
Section: Macroscopic Findingmentioning
confidence: 99%
“…However, few new markers associated with prognosis or malignant behavior of ICC has been determined (Oishi et al 2012;Shimada et al 2010). In this study we studied Nogo-B, which has recently been identified as a potential marker of hepatic fibrosis (Zhang et al 2011;Gao et al 2013;Tashiro et al 2013;Men et al 2015) and as a potential enhancer of bile duct proliferation (Zhang Each survival rate is shown as % value, based on our analytical software.…”
Section: Macroscopic Findingmentioning
confidence: 99%
“…[19]. Recent studies revealed that CD133 is an important cancer stem cell marker of solid tumors including cholangiocarcinoma [20][21][22] and liver tumors [4,23]. In an in-vitro study using a cholangiocarcinoma cell line, CD133-positive cells had higher invasiveness compared with CD133-negative cells [24].…”
Section: Molecular Cholangiocarcinoma Stem Cell Markersmentioning
confidence: 99%
“…Shimada et al [22] analyzed CD133 expression in 29 patients with intrahepatic cholangiocarcinoma. In their study, the 5-year survival rate in the CD133-positive group (8 %) was worse than that in the CD133-negative group (57 %), and the incidence of intrahepatic metastasis was higher in the CD133-positive group.…”
Section: Hepatic Stem Cellmentioning
confidence: 99%
“…CD133-positive cells showed higher invasiveness compared with CD133-negative cells. Shimada et al [75] analyzed CD133 expression in 29 patients with intrahepatic CCA and found that the 5-year survival rate in the CD133-positive group (8%) was worse than that in the CD133-negative group [76]. However, Fan et al [77] reported contrasting results, in which CD133 expression was correlated with a higher tumor diferentiation status in 54 consecutively analyzed CCA specimens.…”
Section: Csc Markers In Ccamentioning
confidence: 99%